PHYSIOCHEMICAL AND PHYTOCHEMICAL ANALYSIS OF ECLIPTA ALBA - NIVEDITA; PRIYANKA VIJAY (International Journal of Pharma and Bio Sciences, 2013)
The present study comprises physicochemical and phytochemical evaluation of arial parts of Eclipta alba in different extracts using ethanol, petroleum ether, benzene, chloroform and aqueous solvents by using standard methods. The physical evaluation was carried out for the determination physiochemical profile such as ash values and extractive values, whereas phytochemical evaluation was carried out for the screening of bioactive compounds in different extracts of E. alba (arial parts). Preliminary phytochemical analysis test showed the presence of carbohydrates, protein, glycosides, saponin, steroids, flavonoids, alkaloids and tannins. Chloroform extract of plant showed the presence of proteins terpenoids, saponin, tannin and steroids. Petroleum ether extract of plant leaf showed the presence of carbohydrates, protein, terpenoids, saponin and steroids. This study will help in development of a suitable monograph, determining the quality and purity of a crude drug and laying down pharmacopoieal standards for E. alba.